Interaction of small molecules with polynucleotide repeats and frameshift site RNA - Nemr, Mohamed T. M.; Yousif, Mahmoud N. M.; Barciszewski, Jan (Archiv der Pharmazie (Weinheim), 2019)
This mini‐review describes the interaction between small molecules and RNA, in addition to its application either in treating RNA‐associated diseases or detecting target molecules. In the case of RNA‐associated disease treatment, the designed small molecules interact with RNA sites, forming adducts and providing successful therapeutic strategies over oligonucleotides. On the other hand, synthetically designed RNA moieties (aptamers) interact with target molecules like toxins, drugs, hormones; these interactions are useful in the detection, quantification or separation of these target moieties. Interaction of small organic heterocyclic compounds with different types of RNA is the subject of our review article. For example, N‐(3‐azidopropyl)‐4‐(3‐(6‐(4‐methylpiperazin‐1‐yl)‐1H,3′H‐[2,5′‐bibenzo[d]imidazol]‐2′‐yl)phenoxy)butanamide (Ht) is a parent compound, which was derivatized to achieve binding with RNA. The review article lists many different small molecules binding to different types of RNA.